2020
DOI: 10.1007/s40037-020-00615-y
|View full text |Cite
|
Sign up to set email alerts
|

Learning from failure: how eliminating required attendance sparked the beginning of a medical school transformation

Abstract: Concern about medical student attendance has been rising over the last decade. Thinking a required attendance policy would fix things, we instituted such a mandate in 2010 only to find that although students were present at lecture and other learning sessions they were disengaged. In addition, we experienced growing distrust between faculty and students and tensions between the Student Affairs and Curriculum offices. After five years, we dismantled the policy in favor of encouraged attendance. We discuss both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…Students who do not attend in-person activities can choose to customize their learning by accessing a variety of resources without impacting performance on assessments [ 17 ]. Lamb et al found that students will attend optional “recommended” activities if they feel it benefits their learning [ 18 ], but that they resent being forced to attend activities that they do not feel benefit them. Developmentally, medical students may be considered adult learners [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Students who do not attend in-person activities can choose to customize their learning by accessing a variety of resources without impacting performance on assessments [ 17 ]. Lamb et al found that students will attend optional “recommended” activities if they feel it benefits their learning [ 18 ], but that they resent being forced to attend activities that they do not feel benefit them. Developmentally, medical students may be considered adult learners [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Research has shown that the association between attendance and academic performance is not clear and is, in fact, variable [15]. Although this has led to differing opinions regarding opting for mandatory attendance in medical schools across the country, rates of attending lectures have been steadily decreasing year to year [16].…”
Section: Attendancementioning
confidence: 99%
“…Since moving to an expected, not required, attendance policy in AY 2016-2017, [30] attendance at CRR large group lectures had declined. However, turnout on paper puzzles days was very high, inspiring the course directors to learn about students' thoughts about paper puzzles.…”
Section: Use Of Paper Puzzles In Classmentioning
confidence: 99%